Enhanced Driving Force and Charge Separation Efficiency of Protonated g‑C3N4 for Photocatalytic O2 Evolution - Ye, Chen; Li, Jia-Xin; Li, Zhi-Jun; Li, Xu-Bing; Fan, Xiang-Bing; Zhang, Li-Ping; Chen, Bin; Tung, Chen-Ho; Wu, Li-Zhu (ACS catalysis, 2015)
Photocatalysts based on g-C3N4 by loading cocatalysts or constructing heterojunctions have shown great potential in solar-driven water oxidation. However, the intrinsic drawbacks of g-C3N4, such as poor mass diffusion and charge separation efficiency, remain as the bottleneck to achieve highly efficient water oxidation. Here we report a simple protonation method to improve the activity of g-C3N4. Studies using valence band X-ray photoelectron spectra and steady-state and time-resolved spectroscopy reveal that the promotion of catalytic ability originates from the higher thermodynamical driving force and longer-lived charge separation state, which may provide guidance in designing efficient polymeric semiconductor photocatalysts with desirable kinetics for water oxidation.